SUB EPIDURAL HEMATOMA IN STROKE: A RARE BUT CRITICAL CONSIDERATION IN ADULT PATIENTS - Negmatova Hilola Mahkamovna (Bright Mind Publishing, 2025)
Sub-epidural hematoma (SEDH) is an uncommon but life-threatening complication that may occur in the context of ischemic or hemorrhagic stroke. Although subdural and intracerebral hemorrhages are well-recognized in stroke pathology, sub-epidural hematoma remains an underreported entity. This article analyzes clinical characteristics, diagnostic approaches, and management strategies for sub-epidural hematoma associated with stroke in adult patients. Based on clinical literature and case analyses, the article highlights the diagnostic challenges and emphasizes the importance of neuroimaging in early recognition to improve outcomes.
Keywords: Sub-epidural hematoma, stroke, neuroimaging, ischemic stroke, intracranial hemorrhage, neurosurgery, adult patients.